Structural analysis of the northern part of the East Anatolian Fault System - Kokum, Mehmet; Inceoz, Murat (Pergamon-Elsevier Science Ltd, 2018)
The East Anatolian Fault System (EAFS) is an intra-continental strike-slip fault associated with the collision of the Arabian plate with the Anatolian plate in the Alp-Himalaya system. In this study, the northern part of the EAFS, was studied. We measure more than two-hundred fault slip data (strike, dip, striation and slip sense for each fault) in eighteen different localities to make paleostress reconstruction of the related area. Several criteria are taken into consideration in order to reveal chronology of faulting such as superimposed slickenlines, age of the affected strata and syndepositional faults. Our results show three different deformation stages from the Middle Eocene to today in the study area: (1) The NW-SE extensional tectonic, oldest stage, became effective in Middle Eocene-Middle Miocene; (2) the NNE-SSW compressional tectonic become effective in Late Miocene Early Pliocene; (3) the strike-slip tectonic, youngest stage, has been effective since Late Pliocene. The maximum compressive stress (sigma(1)) orientation averaged around N25 degrees E and N15 degrees E for Stage 2 and Stage 3, respectively. This ca. 10(0) rotation of the maximum compressive stress (sigma(1)) orientation may be related to the formation of the strike-slip faults concluded changing in the stress orientations between sigma 3 and sigma 2 in the Late Pliocene.
Keywords: Turkey; Paleostress; Slip data; Strike-slip fault